1997
DOI: 10.1034/j.1399-3054.1997.990118.x
|View full text |Cite
|
Sign up to set email alerts
|

Agarose embedding affects cell wall regeneration and microtubule organization in sunflower hypocotyl protoplasts

Abstract: A. and Alibert, G. 1997. Agarose embedding affects cell wall regeneration and microtubule organization in sunflower hypocotyl protoplasts -Physiol. Plant. 99: 129-134.Sunflower hypocotyl protoplasts (Helianthus annuus L. cv. Emil) divide symmetrically to fonn loosely associated microcolonies when cultured in liquid medium, whereas when embedded in agarose beads they divide asymmetrically to give rise to embryo-like structures. To understand the relationship between protoplast embedding and cell division patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…For instance, sunflower protoplasts cultured in liquid medium form loosely associated cells and do not embark on the embryogenic pathway. However, when the same cells are embedded in agarose, they start to deposit callose at their reforming cell walls, assemble numerous perinuclear microtubules, and enter the embryogenic pathway (Caumont et al 1997). It would be interesting to know whether these callosic cell walls also accumulate some AGPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, sunflower protoplasts cultured in liquid medium form loosely associated cells and do not embark on the embryogenic pathway. However, when the same cells are embedded in agarose, they start to deposit callose at their reforming cell walls, assemble numerous perinuclear microtubules, and enter the embryogenic pathway (Caumont et al 1997). It would be interesting to know whether these callosic cell walls also accumulate some AGPs.…”
Section: Discussionmentioning
confidence: 99%
“…They are also abundant in Arabidopsis mutants with affected cell growth polarity and morphogenesis (Hauser et al 1995;Traas et al 1995). Numerous endoplasmic microtubules are present in cells treated with auxin (for maize roots see BaluÐka et al 1996b) or subjected to diverse stresses including cold (BaluÐka et al 1993), heat (Hause et al 1993;Gervais et al 2000), mechanical stress (Caumont et al 1997), and aluminium (Sivaguru et al 1999). Similarly, during sporogenesis (Dickinson and Sheldon 1984), endosperm development (Brown and Lemmon 1988;Brown et al 1994), and Rhizobium infection (Timmers et al 1999), centered nuclei organize almost all microtubules in the form of radial arrays.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, physical constraints cannot solely explain the protoplast division pattern observed in agarose cultures. Recently, in a study of the cytoskeleton of agaroseembedded protoplasts, Caumont et al (1997) reported that the agarose matrix interacts with cortical microtubules and stabilizes the cytoskeleton. In animal cells, it is well known that several plasma membrane proteins are involved in linkages of the cytoskeleton to the extracellular matrix, the most prominent and best studied matrix receptors belonging to the integrin family (Hynes 1992 (Henry et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In sunflower, somatic embryogenesis is also an important tool, enabling the analysis of embryo development outside the maternal environment (Scheres and Benfey 1999;Vroemen et al 1999). An experimental system in which, depending on the culture conditions, an isolated cell (protoplast) can give rise to somatic tissues or to embryo-like structures has also been developed in sunflower (Caumont et al 1997).…”
Section: Introductionmentioning
confidence: 99%